Thyroid disrupting chemicals during pregnancy: an invitation to collaborate in the consortium on thyroid and pregnancy - Arash Derakhshan; Akhgar Ghassabian; Leonardo Trasande; Tim I. M. Korevaar (Thyroid Research)
Abstract This is an invitation letter for the principal investigators and cohort studies to join the Consortium on Thyroid and Pregnancy. The inclusion criteria are population-based cohorts with data on maternal thyroid function during pregnancy and any measurement of known groups of endocrine disrupting chemicals.